Sola Scriptura : biblical and theological perspectives on scripture, authority, and hermeneutics - Burger, Hans, 1974- (Studies in Reformed Theology, 2017)
Sola Scriptura offers a multi-disciplinary reflection on the theme of the priority and importance of Scripture in theology, from historical, biblical-theological and systematic-theological perspectives, aiming at the interaction between exegesis and dogmatics. Brian Brock and Kevin J. Vanhoozer offer concluding reflections on the theme, bringing the various contributions together.